2018
DOI: 10.1093/ajcn/nqx045
|View full text |Cite
|
Sign up to set email alerts
|

Nudging and social marketing techniques encourage employees to make healthier food choices: a randomized controlled trial in 30 worksite cafeterias in The Netherlands

Abstract: This study shows that the way worksite cafeterias offer products affects purchase behavior. Situated nudging and social marketing-based strategies are effective in promoting healthier choices and aim to remain effective over time. Some product groups only indicated an upward trend in purchases. Such an intervention could ultimately help prevent and reduce obesity in the Dutch working population. This trial was registered at the Dutch Trial Register (http://www.trialregister.nl/trialreg/admin/rctview.asp?TC=537… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 36 publications
2
47
0
Order By: Relevance
“…Choice architecture has been discovered as a way of influencing consumer choice [21][22][23]. By changing the choice architecture, the freedom to choose should be preserved according to the libertarian paternalism view of Thaler and Sunstein [22].…”
Section: Choice Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…Choice architecture has been discovered as a way of influencing consumer choice [21][22][23]. By changing the choice architecture, the freedom to choose should be preserved according to the libertarian paternalism view of Thaler and Sunstein [22].…”
Section: Choice Architecturementioning
confidence: 99%
“…Choice architecture may be accomplished in different ways. For example, to increase consumer preference, products could be placed at eye-level [23][24][25], presented in separate categories or interspersed with other categories [26], or given particular colors (say, green for sustainable products). Additionally, normative messages showing that most people prefer a particular product [27] or narrative could be added to make product options more attractive [28].…”
Section: Choice Architecturementioning
confidence: 99%
“…11,12,13 Choice architecture (eg, product placement) interventions make it easier and more convenient for employees to choose a healthy item without having to consider detailed nutrition information. 7,12,14 Both strategies have been shown to promote healthier food purchases in workplace settings. 7,12,15…”
Section: Introductionmentioning
confidence: 99%
“…This relative small improvement corresponds to findings of other canteen or retail interventions in various settings. For example, a randomized controlled trial in worksite cafeterias in the Netherlands showed similar increased sales figures, particularly for sandwiches, cheese and fruit [28]. A recent intervention study in worksite cafeterias in the United Kingdom in which the proportion of healthier foods available was increased showed a reduction of almost 7% in energy purchased from targeted food products [29].…”
Section: Discussionmentioning
confidence: 94%